2022
DOI: 10.1038/s41598-022-09426-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pancreatitis and cancer risk in a matched cohort study using national claims data in South Korea

Abstract: This study aimed to examine the association between chronic pancreatitis (CP) and cancer incidence and mortality among the Korean population. Based on a cancer-free cohort of 8,317,616 individuals between 2002 and 2010, a matched cohort study was conducted, including 10,899 patients with CP, matched for sex and age with 32,697 individuals without CP. The case and control groups were followed up until the date of onset of cancer or death or the end of follow-up date (December 31, 2018). Cox proportional hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…It has been demonstrated that PSCs play a vital role in the development of fibrosis and its progression and, thus, impacts pancreatic acinar cells and immune cell activation [ 10 , 12 , 19 , 49 , 55 , 56 , 57 , 58 ]. Chronic pancreatitis is a risk factor for pancreatic cancer, and mutations in the proto-oncogene KRAS are found in nearly all cases of pancreatic cancer [ 59 , 60 , 61 ]. Importantly, mutations of KRAS are often found in early neoplastic lesions resulting from chronic pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that PSCs play a vital role in the development of fibrosis and its progression and, thus, impacts pancreatic acinar cells and immune cell activation [ 10 , 12 , 19 , 49 , 55 , 56 , 57 , 58 ]. Chronic pancreatitis is a risk factor for pancreatic cancer, and mutations in the proto-oncogene KRAS are found in nearly all cases of pancreatic cancer [ 59 , 60 , 61 ]. Importantly, mutations of KRAS are often found in early neoplastic lesions resulting from chronic pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies on the incidence and relative risk of pancreatic cancer in patients with CP. The reported incidence of pancreatic cancer varied from study to study at 0.68‒2.94% 2 , 9 , 10 , 12 , 15 . There are many causes for this variation, and approaches to select patients with CP and the included CPs are the main cause.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter retrospective study, patients who underwent surgery for the treatment of CP had significantly lower incidences of pancreatic cancer 5 . A recent published study in South Korea registered patients using only ICD-10 codes and reported a low pancreatic cancer incidence of 0.68% 15 . As observed in our study, a notable number of CP patients registered with only ICD code K86 might not have CP, and even if they had CP, the CP could be probable or borderline CP instead of definite CP.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter retrospective study, patients who underwent surgery for the treatment of CP had signi cantly lower incidences of pancreatic cancer 5 . A recent published study in South Korea registered patients using only ICD-10 codes and reported a low pancreatic cancer incidence of 0.68% 15 . As observed in our study, a notable number of CP patients registered with only ICD code K86 might not have CP, and even if they had CP, the CP could be probable or borderline CP instead of de nite CP.…”
Section: Discussionmentioning
confidence: 99%